Life-Threatening Hypercalcemia Revealing Diffuse and Isolated Acute Sarcoid-Like Myositis: A New Entity? (A Case-Series). Issue 10 (March 2016) - Mageau, Arthur; Rigolet, Aude; Benali, Khadija; Chauchard, Maria; Ladjeroud, Salima; Mahe, Isabelle; Maisonobe, Thierry; Chauveheid, Marie-Paule; Papo, Thomas; Sacre, Karim
Abstract : Abstract: Up to 50% patients with sarcoidosis display extra-pulmonary disease. However, initial and isolated (ie, without lung disease) acute muscular involvement associated with pseudo-malignant hypercalcemia is very uncommon. We report on 3 cases of life-threatening hypercalcemia revealing florid and isolated acute sarcoid-like myositis. All patients complained of fatigue, progressive general muscle weakness, and weight loss. Laboratory tests showed a severe life-threatening hypercalcemia (>3.4 mmol/L). Hypercalcemia was associated with increased serum level of 1, 25-(OH)2 vitamin D and complicated with acute renal failure. One patient displayed acute pancreatitis due to hypercalcemia. In all cases, PET-scan, performed for malignancy screening, incidentally revealed an intense, diffuse, and isolated muscular fluorodeoxyglucose (FDG) uptake consistent with diffuse non-necrotizing giant cells granulomatous myositis demonstrated by muscle biopsy. Of note, creatine phosphokinase blood level was normal in all cases. No patients displayed the usual thoracic features of sarcoidosis. All patients were treated with high dose steroids and achieved rapid, complete, and sustained remission. A review of English and French publications in Medline revealed 5 similar published cases. Steroid-sensitive acute sarcoid-like myositis causing high calcitriol levels and life-threatening hypercalcemia should be recognized as a separate entity.